Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT Pelita Air Service - Eko Mei Purwanto; Jaelani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of organizational culture and work discipline on employee performance at PT Pelita Air Service. In the aviation industry, which requires high standards of safety, punctuality, and service quality, employee performance plays a crucial role in supporting organizational success. Organizational culture and work discipline are considered important factors that shape employee behavior and influence the quality of work outcomes. This research employs a quantitative approach with an associative method. The population of this study consists of all employees of PT Pelita Air Service working in the Operation Control Center (OCC), Ground Operations, and Maintenance divisions, totaling 83 employees. A total sampling technique was applied, in which the entire population was used as research respondents. Data were collected through observation and questionnaires using a Likert scale. Data analysis techniques included descriptive analysis, validity and reliability tests, classical assumption tests, and multiple linear regression analysis to test the research hypotheses. The results of this study are expected to provide empirical evidence regarding the extent to which organizational culture and work discipline affect employee performance at PT Pelita Air Service. The findings are expected to serve as a reference for company management in formulating effective human resource management policies to improve employee performance and support the achievement of organizational goals.